Democratic literacy: Challenges and opportunities to engage youth participatory in the age of digital media - Ribut Santoso, Nobertus; Lewi Pramesti, Olivia; Bestari Puspita, Birgitta; Diyah Wulandari, Theresia (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
This study endeavors to ascertain the challenges and opportunities in democracy literacy to foster active youth engagement in the digital media age. Through the implementation of Focus Group Discussions and participatory workshops involving a cohort of 17 participants, comprising eight student journalists and nine non-student journalists, who are poised to exercise their voting rights for the first time during the forthcoming 2024 elections, the research outcomes divulge that disparities exist in the democratic perspectives of student and non-student journalists, primarily due to their contrasting experiences. Nevertheless, both groups concur that a solid understanding of democratic principles empowers them to partake in the democratic process. In the digital media era context, four notable challenges emerge in democratic literacy: hoax oasis, politician stigmatization, idiot discussion engagement, and political apathy engagement. Conversely, two prospective avenues for bolstering democratic literacy are identified: information oasis and reigniting youth participation. These identified challenges and opportunities serve as fundamental pillars for formulating effective democratic literacy strategies in the digital era, thereby fostering increased participation of young voters in democratic practices.